Effects of estrogen and venlafaxine on menopause-related quality of life in healthy postmenopausal women with hot flashes. Issue 6 (June 2015) - Caan, Bette; LaCroix, Andrea Z.; Joffe, Hadine; Guthrie, Katherine A.; Larson, Joseph C.; Carpenter, Janet S.; Cohen, Lee S.; Freeman, Ellen W.; Manson, JoAnn E.; Newton, Katherine; Reed, Susan; Rexrode, Kathy; et al.
Abstract Objective This study aims to evaluate the effects of low-dose estradiol (E2) or venlafaxine on menopause-related quality of life and associated symptoms in healthy perimenopausal and postmenopausal women with hot flashes. Methods A double-blind, placebo-controlled, randomized trial of low-dose oral 17β-E2 0.5 mg/day and venlafaxine XR 75 mg/day, versus identical placebo, was conducted among 339 women (aged 40-62 y) experiencing two or more vasomotor symptoms (VMS) per day (mean [SD], 8.07 [5.29]) who were recruited at three clinical sites from November 2011 to October 2012. The primary trial outcome, as reported previously, was frequency of VMS at 8 weeks. Here, we report on secondary endpoints of total and domain scores from the Menopause-Specific Quality of Life Questionnaire (MENQOL) and from measures of pain (Pain, Enjoyment in life, and General activity scale), depression (Patient Health Questionnaire-9), anxiety (Generalized Anxiety Disorder Questionnaire-7), and perceived stress (Perceived Stress Scale). Results Treatment with both E2 and venlafaxine resulted in significantly greater improvement in quality of life, as measured by total MENQOL scores, compared with placebo (E2: mean difference at 8 wk, −0.4; 95% CI, −0.7 to −0.2; P < 0.001; venlafaxine: mean difference at 8 wk, −0.2; 95% CI, −0.5 to 0.0; P = 0.04). Quality-of-life domain analyses revealed that E2 had beneficial treatment effects on all domains of the MENQOL except for the psychosocial domain, whereas venlafaxine benefits were observed only in the psychosocial domain. Neither E2 nor venlafaxine improved pain, anxiety, or depressive symptoms, although baseline symptom levels were low. Modest benefits were observed for perceived stress with venlafaxine. Conclusions Both low-dose E2 and venlafaxine are effective pharmacologic agents for improving menopause-related quality of life in healthy women with VMS.